"Daddy, Help Me; I Forgot How to Make a New Friend": Emotional Geographies of Youth Sport in Pandemic Times. (October 2021) - Giardina, Michael D.
In what follows, the author directs attention to one slice of pandemic life and its interplay across the emotional geographies of childhood, parenthood, work-life balance, lockdowns, stress, mental health, and youth sport, for it is in these private if banal moments that the "everyday" experiences of the pandemic are made real—and reveal the tensions and dilemmas that individuals tried to negotiate—to differing levels of success.